Control of Metal Trading Activities, in Particular the Purchase of Scrap Metal - Rózsa, Attila; Darabos, Éva (International Journal of Engineering and Management Sciences, 2017)
Over the past decade, the metal trade was a frequented area of the black economy. The transformation of the legal background of registration and reporting obligations has played an important role in the change of the situation. There were several steps taken to whiten metals trade such as introduction of the reverse charge, then a few years later, the possibility of nationalization, the metal Act and the related decree. From the impact of all these the authors introduce the influence of registration and reporting obligations related to certain acquisitions of enterprises engaged in metal trading activities.